2023
DOI: 10.3389/fcell.2023.1112319
|View full text |Cite
|
Sign up to set email alerts
|

Septins as membrane influencers: direct play or in association with other cytoskeleton partners

Abstract: The cytoskeleton comprises three polymerizing structures that have been studied for a long time, actin microfilaments, microtubules and intermediate filaments, plus more recently investigated dynamic assemblies like septins or the endocytic-sorting complex required for transport (ESCRT) complex. These filament-forming proteins control several cell functions through crosstalks with each other and with membranes. In this review, we report recent works that address how septins bind to membranes, and influence the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 155 publications
1
18
0
Order By: Relevance
“…During plasma membrane repair, the remodeled septins closely associate with F-actin, myosin IIA, and ANXA2 throughout the cell surface and within the septin knobs and loops (Figures 2 to 5 and SF 4 to 6). Super-resolution microscopy allowed for visualization of intertwined F-actin and septin filaments in the septin loops (Figure 5), in accordance with the role of septins in bending actin filaments [25]. The septins mostly run parallel to the F-actin and, at times, appear perpendicular as if interconnecting actin fibers (Figure 5).…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…During plasma membrane repair, the remodeled septins closely associate with F-actin, myosin IIA, and ANXA2 throughout the cell surface and within the septin knobs and loops (Figures 2 to 5 and SF 4 to 6). Super-resolution microscopy allowed for visualization of intertwined F-actin and septin filaments in the septin loops (Figure 5), in accordance with the role of septins in bending actin filaments [25]. The septins mostly run parallel to the F-actin and, at times, appear perpendicular as if interconnecting actin fibers (Figure 5).…”
Section: Discussionmentioning
confidence: 67%
“…We found that SEPT2, SEPT7, and SEPT9 display similar labeling patterns in all experimental conditions. This was expected since septins of different groups co-assemble to form hexamers (SEPT-2,-6,-7,-7,-6,-2) and octamers (SEPT- 2,-6,-7,-9,-9,-7,-6,-2) [25]. We observed that septin filaments predominantly colocalized with actin stress fibers in control untreated cells (Figure 2Aa, SF 4Aa, Ba).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations